Catalysing net-zero retrofit: feasibility of an innovative salary sacrifice scheme - Topouzi, M; Mallaburn, P; Fawcett, T (Centre for Research into Energy Demand Solutions, 2023)
The shift towards hybrid working-from-home practices is seen by the authors as a great opportunity to introduce a novel financial mechanism, the Retrofit Salary Sacrifice (RSS) scheme that will help increase homeowners’ awareness and uptake of retrofit works to improve their home-office environments. This novel approach is to encourage household-level retrofitting in order to reduce carbon emissions and lower energy costs (Figure 1). It is a tax-efficient incentive for home-owning employees to improve their properties, using the model of successful existing salary sacrifice schemes for the purchase of bicycles and EVs. This approach has a catalytic role for able-to- pay salaried homeowners to directly benefit from more attractive and affordable finance for retrofit projects, the prospect of lower energy bills in the long term, and a more comfortable working environment. Additionally, employers gain an extra benefit to offer their workforce, as well as a route to addressing Scope 1–3 of their direct and indirect carbon emissions. This report presents results from work exploring the value of an RSS scheme to different stakeholder groups, assessing its feasibility for piloting and/or implementation, and understanding what needs to be in place for a successful RSS trial. Project activities leading to these specific outcomes involved ongoing conversations, online surveys, and a half-day workshop with key individuals from various groups in central and local government, the construction sector/supply chain, banks/lenders, and employers/companies, along with employees/homeowners.